Crustal evolution of a continental magmatic arc from subduction to collision: a case study in the Gangdese arc, southern Tibetan Plateau - Zhang, Z-M; Ding, H-X; Palin, RM; Dong, X; Tian, Z-L; Li, X-W (Geological Society of America, 2024)
Magmatic arcs are the main environment where continental crust is created on the post-Archean Earth; however, how juvenile arc crust evolves into mature continental crust is still controversial. In this study, we report new bulk-rock major and trace elements, Sr-Nd isotopes, and zircon U-Pb ages and Hf isotopes from a large suite of granites collected from the eastern segment of the Gangdese arc, southern Tibetan Plateau, which record a complete history of arc crust evolution from Mesozoic subduction to Cenozoic collision. These new data show that Gangdese crust-derived granites generated during the subduction to collisional stages record significant geochemical changes with age, indicating that the bulk composition, lithological makeup, and thicknesses of the arc crust evolved over time. Here, we propose that the Gangdese arc had a thick juvenile crust with a small volume of ancient crustal components during late-stage subduction of the Neo-Tethys Ocean, a thin juvenile crust with heterogeneously distributed ancient crustal materials during early collision, and a thick juvenile crust with minor proportions of ancient rocks during late collision. This implies that the arc experienced episodes of crustal thickening during the Late Cretaceous and Eocene, interspersed by periods of thinning during the Paleocene and Miocene, and several discrete episodes of partial melting in the lower arc crust, and cycling or recycling of juvenile and ancient crustal materials within the arc crust and between the crust and mantle. We suggest that shallow subduction of the Neo-Tethys during the Late Cretaceous promoted tectonic thickening of the arc crust, partial melting of lower crust, and formation of high Sr/Y granites. After the onset of the Indo-Asian collision, breakoff of the subducted Neo-Tethyan oceanic slab during the Paleocene/early Eocene allowed thinning of the overlying arc crust and generation of granites derived from juvenile and ancient crustal sources. Continued underthrusting of the Indian continental crust and subsequent delamination of thickened lithospheric mantle led to thickening and thinning of the arc crust, respectively, and partial melting of thickened lower crust and generation of high Sr/Y granites during the Oligocene and Miocene. Using the Gangdese as an analogue for post-Archean continental margins, we suggest that the repeated thickening and thinning of arc crust, and associated multistage remelting of the lower arc crust, and material cycling or recycling within the crust and between the crust and mantle from subduction to collision are common processes that drive maturation of juvenile arc crust.